Pulmonary Vein Variation: A Case report study - Amirabbas Gharibi; Firoozeh Niazvand (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Īlām)
Introduction:  The heart consists of four chambers: the right atrium, right ventricle, left atrium, and left ventricle. Pulmonary veins return oxygenated blood from the lungs to the left atrium, typically through four veins—two from each lung—entering the left atrium independently. Awareness of these variations is crucial for clinicians, particularly in procedures involving pulmonary veins and cardiac arrhythmias. This report presents a cadaveric case demonstrating an anatomical variation of the pulmonary veins. Case Report: During routine cadaveric dissection in the anatomy laboratory, an anatomical variation was observed in a male cadaver estimated to be between 65 and 70 years of age. Two pulmonary veins from the left lung exhibited an anastomosis before entering the pericardial cavity and subsequently drained into the left atrium as a single vessel. The course and position of all other cardiac and adjacent thoracic structures were found to be normal, with no additional anatomical anomalies and variations. Conclusion: This case emphasizes the importance of recognizing anatomical variations in pulmonary venous drainage. Comprehensive knowledge of thoracic anatomy, including rare vascular patterns, is essential for accurate diagnosis, surgical planning, and avoiding potential intraoperative complications.